Are value–behavior relations stronger than previously thought? It depends on value importance. Issue 2 (March 2022) - Lee, Julie Anne; Bardi, Anat; Gerrans, Paul; Sneddon, Joanne; van Herk, Hester; Evers, Uwana; Schwartz, Shalom
Research has found that value–behavior relations are usually weak to moderate. But is this really the case? This paper proposes that the relations of personal values to behavior are stronger at higher levels of value importance and weaker at lower levels. In a large, heterogeneous sample, we tested this proposition by estimating quantile correlations between values and self-reported everyday behavior, at different locations along the distribution of value importance. We found the proposed pattern both for self-reports of everyday behaviors chosen intentionally to be value-expressive and everyday behaviors subject to strong situational constraints (e.g., spending allocation to clothing and footwear). Our findings suggest that value–behavior relations may be stronger than previously recognized, depending on value importance. People who attribute high importance to a value will not only engage in value-expressive behaviors more frequently, but as we move up the value importance distribution, the relations strengthen. In contrast, people who attribute low importance to a value not only engage in value-expressive behaviors less frequently, but as we move down the value importance distribution, the relations weaken. These findings provide important insight into the nature of values.